Comparing internal jugular vein and subclavian vein for central venous insertion of implantable ports in cancer chemotherapy: a meta-analysis of RCTs - Li, Qianqian; Peng, Xuemei; Leng, Xia; Xiao, Suping; Min, Meilan; Wan, Shufang; Wen, Jianyun (Frontiers in Oncology, 2025)
BackgroundCentral venous access for cancer chemotherapy is crucial for patients undergoing long-term treatment. The internal jugular vein (IJV) and subclavian vein (SCV) are commonly used for implantable port insertion, though the optimal choice remains debated. This meta-analysis aims to compare the safety and effectiveness of IJV and SCV for central venous implantable port insertion in cancer chemotherapy patients based on randomized controlled trials (RCTs).MethodsWe systematically reviewed RCTs comparing IJV and SCV for implantable port insertion. The primary endpoint was complication, while secondary endpoints included procedure failure rate, procedure duration, patient satisfaction, and pain perception.ResultsA total of 7 studies based on 6 RCTs met the inclusion criteria. The baseline characteristics (age, sex, port side, and duration of implant) of patients in both groups were comparable. According to patient-reported outcomes, the SCV group experienced higher rates of total complications (risk ratio [RR]: 0.52 [0.29, 0.93], P = 0.03, I2 = 71%), catheter misplacement (RR: 0.51 [0.27, 0.96], P = 0.04, I2 = 35%), and port/catheter-related bloodstream infections (RR: 0.37 [0.17, 0.81], P = 0.01, I2 = 0%). Similarly, according to catheter days, the SCV group achieved higher rates of total complications (RR: 0.48 [0.35, 0.67], P < 0.0001, I2 = 29%) and port/catheter-related bloodstream infections (PRBIs) (RR: 0.32 [0.14, 0.72], P = 0.006, I2 = 0%). Pain perception (mean difference [MD]: -1.60 [-1.93, -1.27], P < 0.00001) was also worse in the SCV group. However, the duration of the procedure (MD: 11.55 [0.57, 22.54] minutes, P = 0.04, I2 = 97%) was longer in the IJV group. The procedural failure rate was comparable between the two groups.ConclusionsFor cancer chemotherapy patients, the IJV appears to be a safer and less painful alternative to the SCV for central venous port insertion.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025641904.